Retrospective methods to estimate radiation dose at the site of breast cancer development after Hodgkin lymphoma radiotherapy. (December 2017) - Russell, Nicola S.; Krul, Inge M.; van Eggermond, Anna M.; Aleman, Berthe M.P.; Cooke, Rosie; Kuiper, Susanne; Allen, Steven D.; Wallis, Matthew G.; Llanas, Damien; Diallo, Ibrahima; de Vathaire, Florent; Smith, Susan A.; et al.
Abstract: Background: An increased risk of breast cancer following radiotherapy for Hodgkin lymphoma (HL) has now been robustly established. In order to estimate the dose–response relationship more accurately, and to aid clinical decision making, a retrospective estimation of the radiation dose delivered to the site of the subsequent breast cancer is required. Methods: For 174 Dutch and 170 UK female patients with breast cancer following HL treatment, the 3-dimensional position of the breast cancer in the affected breast was determined and transferred onto a CT-based anthropomorphic phantom. Using a radiotherapy treatment planning system the dose distribution on the CT-based phantom was calculated for the 46 different radiation treatment field set-ups used in the study population. The estimated dose at the centre of the breast cancer, and a margin to reflect dose uncertainty were determined on the basis of the location of the tumour and the isodose lines from the treatment planning. We assessed inter-observer variation and for 47 patients we compared the results with a previously applied dosimetry method. Results: The estimated median point dose at the centre of the breast cancer location was 29.75 Gy (IQR 5.8–37.2), or about 75% of the prescribed radiotherapy dose. The median dose uncertainty range was 5.97 Gy. We observed an excellent inter-observer variation (ICC 0.89 (95% CI: 0.74–0.95)). The absolute agreement intra-class correlation coefficient (ICC) for inter-method variation was 0.59 (95% CI: 0.37–0.75), indicating (nearly) good agreement. There were no systematic differences in the dose estimates between observers or methods. Conclusion: Estimates of the dose at the point of a subsequent breast cancer show good correlation between methods, but the retrospective nature of the estimates means that there is always some uncertainty to be accounted for.